If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3.17x + 1.11 = 2.8x Reorder the terms: 1.11 + 3.17x = 2.8x Solving 1.11 + 3.17x = 2.8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2.8x' to each side of the equation. 1.11 + 3.17x + -2.8x = 2.8x + -2.8x Combine like terms: 3.17x + -2.8x = 0.37x 1.11 + 0.37x = 2.8x + -2.8x Combine like terms: 2.8x + -2.8x = 0.0 1.11 + 0.37x = 0.0 Add '-1.11' to each side of the equation. 1.11 + -1.11 + 0.37x = 0.0 + -1.11 Combine like terms: 1.11 + -1.11 = 0.00 0.00 + 0.37x = 0.0 + -1.11 0.37x = 0.0 + -1.11 Combine like terms: 0.0 + -1.11 = -1.11 0.37x = -1.11 Divide each side by '0.37'. x = -3 Simplifying x = -3
| 364=8b-5(8b+4) | | 5(a+2)(a-4)=0 | | -32-49-3x=-12x | | 9z^2-54z+76= | | 96=8(6-a) | | u=4.20-0.75s | | 6m-8=4-3m | | 12x-4(x+4)=3+5(4x+1) | | 12x-4(x-4)=3+5(4x+1) | | 47a+56=-320 | | 12+5m=-3 | | x-(8x+5)=15+2(11-7x) | | 3+2x=3(2x+4)-5(x-2) | | 3x-(8-x)=5(3-x)+4 | | -7+2x=-25-x | | x-(8-x)=5(3-x)+4 | | 10+12=-34+x | | 2x+10-7x=3(x-5)+1 | | 3*(x+2)=3x+32 | | 7(2x+1)=5x+16 | | 9x+8+2x+6=7x+2 | | 8x-5x=8 | | 10p-4=86 | | -7+8x-19=15+3(x-17) | | 5/m=8/6 | | 2[t+6]-1=9 | | 3/n=10/7 | | x+8(12-x)=7x-(5x-42) | | 6/a=5/7 | | -16=-4[v+3] | | 1/2-3x=-1/2 | | -4+5x=36 |